PROBLEMA GURU PEMBIMBING KHUSUS DALAM PENYELENGGARAAN PROGRAM PEMBELAJARAN INDIVIDUAL BAGI ANAK BERKEBUTUHAN KHUSUS DI SD N 14 KOTO PANJANG - Miftahul Jannah (Universitas Negeri Padang, 2015)
This research was done due to the findings in the field related to the learning process conducted by the special guidance teachers for the students with special needs at SD N 14 Koto Panjang. . In the learning process, the students were guided classically for their similar ability and similar difficulties. The learning programs were designed and applied as individual learning program (called as PPI) for the students with special needs. This research focused on the problems faced by the special guidance teachers to conduct Individual Learning Program in the form of planning, acting and evaluating. This was a descriptive qualitative research. The informants of the research were the special guidance teachers. The results of the research showed that the special guidance teachers taught in the special classes. the special guidance teachers was less sufficient and the teachers taught in the special classes were less experienced to create appropriate learning activities for the students with special needs. Therefore, it was expected to the teachers to have more understanding on the process of planning, acting and evaluating of individual learning program.Keywords: special guidance teachers; individual learning program; students with special needs